Editorial: Host-pathogen interactions at the blood-brain barriers - Schwerk, Christian; Coisne, Caroline; Mogk, Stefan; Wang, Xiangru (Frontiers in Cellular and Infection Microbiology, 2024)
The human brain requires a well-defined homeostasis for proper operation. To guarantee undisturbed 17 function, specific barriers separate the central nervous system (CNS) from the remainder of the human 18 body. These so-called blood-brain barriers include the "classical" blood-brain barrier (BBB) that is 19 formed by the endothelium of the brain microvasculature, supported by astrocytes and pericytes, and 20 the blood-cerebrospinal fluid barriers (BCSFBs) located at the epithelium of the choroid plexus (CP), 21 the outer layer of the arachnoid membrane, and blood vessels in the subarachnoid space. In their 22 entirety these form a "physical barrier" by hindering a paracellular passage between cells, a 23 "biochemical barrier" due to specific expression of cellular transporters, and an "immunological 24 barrier" by regulating the traffic of immune cells into the CNS. 25Although the BBB and the BCSFB are highly successful in their task to serve and protect the human 26 brain, diverse pathogens have developed strategies to overcome these barriers to enable their own entry 27 into the CNS. Arriving there, these pathogens find an immune-specialized space that offers them an 28 advantage for survival und propagation, ultimately resulting in host diseases as meningitis, encephalitis 29 and meningoencephalitis. To enter the CNS, the pathogens will undergo specific interactions with host 30 cells at the BBB and the BCSFB. 31Coxsackieviruses are considered as one of the leading causes of aseptic meningitis. Brain Barriers" provide insights into the multiple processes involved during brain entry at the blood-84 brain barriers by pathogens as diverse as viruses, bacteria and fungi. A deeper understanding of these 85 host-pathogen interactions will help to understand the pathogenesis and pathophysiology of CNS 86 diseases caused by pathogens and to develop treatment options. In parallel, more and more research 87 data report on the relationship between pathogen-associated inflammation and the pathogenesis of 88 several neurodegenerative diseases, such as PK, Multiple Sclerosis or others, that argue for further 89 investigations. The manuscript published here mainly cover processes at the BBB, certainly an 90 increased emphasis for research also on the BCSFB at the CP and the arachnoid mater would further 91 contribute to gain knowledge on this important topic.